2000
DOI: 10.1677/joe.0.1670403
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the IGF system in a primary adult human skeletal muscle cell model, and comparison of the effects of insulin and IGF-I on protein metabolism

Abstract: In an attempt to address the complex and clinically challenging question of the causes of muscle wasting in patients with cachexia, we have developed a primary adult human skeletal muscle cell model. The cultured cells were characterised by immunocytochemistry using antibodies to the myofibrillar protein constituents desmin and titin. Myotube formation was confirmed biochemically by a fourfold increase in the activity of the muscle-specific enzyme creatinine kinase, and myoblast withdrawal from the cell cycle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
3
35
0
1
Order By: Relevance
“…The vast majority of in vitro and in vivo studies have indicated that IGF-I stimulates muscle protein synthesis (19,26,38,65). This effect is consistent with the well-established role of IGF in adding new synthetic capacity to muscle fibers by incorporation of new muscle nuclei via stimulation of myoblast or satellite cell proliferation and differentiation (5,12).…”
Section: Discussionsupporting
confidence: 74%
“…The vast majority of in vitro and in vivo studies have indicated that IGF-I stimulates muscle protein synthesis (19,26,38,65). This effect is consistent with the well-established role of IGF in adding new synthetic capacity to muscle fibers by incorporation of new muscle nuclei via stimulation of myoblast or satellite cell proliferation and differentiation (5,12).…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, IGF-II gene expression was decreased in turkey satellite cells from proliferation to differentiation (Ernst et al, 1996). In addition, IGF-I expression was not detected in humans (Crown et al, 2000) or avian (Kocamis et al, 2001) satellite cells. The expression patterns of IGF for in vitro muscle cells suggested autocrine regulation of myogenesis by IGFs (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have confirmed that the IGF-1 and insulin signaling pathways play important roles in the proliferation of myoblasts and the progression of myogenesis. IGF-1 and insulin have been shown to stimulate the proliferation and differentiation of muscle cells in a time-and concentrationdependent manner (Allen et al, 1985;Cassar-Malek et al, 1999;Cen et al, 2008;Engert et al, 1996;Grabiec et al, 2014); these important mediators also modulate protein metabolism (Castillo et al, 2004;Crown et al, 2000;Fryburg, 1994). Moreover, the myogenesis program can be influenced when the expression of IGF-1 and insulin receptors are altered (Arabkhari et al, 2010;Bonnesen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%